Heroism Values in Indonesian History Textbooks Indonesian History Grade XI Curriculum 2013 - Ryanto, Ammar Zhafran; Bahri, Samsul (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
Indonesia has experienced colonialism from Europeans and Japanese occupation. Europeans initially sought spices in eastern Indonesia. Over time, Europeans wanted to control these goods which then tried to control the territory of Indonesia which was famous for its natural wealth. Kingdoms/sultanates that previously controlled parts of Indonesia began to experience unrest. Then came the heroic attitude, an attitude that fought for the rights and territories it controlled without interference from other parties. In the field of education, the concept of heroism is instilled through material in school textbooks. Through this research, the author analyzes the compulsory textbook of Indonesian History grade XI based on the 2013 curriculum. This book consists of seven chapters and the author analyzes the value of heroism in several chapters of this book. The purpose of this research is to analyze the values of heroism in the textbook. This research uses a qualitative approach with a discourse analysis method, with history textbooks as the subject. Based on the analysis, it is found that some passages contain the value of heroism. The author can conclude that the Indonesian history textbook grade 11 in 2013 contains the value of heroism.